Performance Fuzzy Logic Control to Minimize Output Voltage Ripple and Balanced Current Distribution of DC-DC Converters in Parallel Non-Identical - Bambang Suprianto; Mochamad Ashari; Mauridhi Hery Purnomo (IPTEK The Journal for Technology and Science, 2010)
Analysis of DC-DC converters are arranged in parallel with the inductor parameters which are different from what discussed in this paper. Buck DC-DC converter using non-identical model, that is different in the value of inductance which is L1 ≠ L2 ≠ L3. Research techniques are taken from the difference of current flows of each converter i.e. I1-I2 and I1- I3 and the reference current is I1. This current difference results are used as input controller. PID and Fuzzy Inference System with 5 gbell membership function are used as a controller. The results of this study indicate a significant system performance. Output voltage ripple is 10 mV with the total output current is 63.7 Ampere. Each DC-DC converter provides a current of contribution to the load 21.28 Ampere. The difference of the current distribution of each converter module range is 1mA - 4mA RMS (Root Mean Square) using PID control, while using Fuzzy Logic Control for differences in the distribution of current is 0.1 mA RMS and the output voltage is 48 volt. Fuzzy Logic Control performance has shown an improvement of control systems to reduce the output voltage ripple and the ability to share load current equally into each DC-DC converter.